2022
DOI: 10.1111/imj.15107
|View full text |Cite
|
Sign up to set email alerts
|

End‐of‐life intravenous chemotherapy administration patterns in the treatment of Queensland lung and pancreas cancer patients: a 10‐year retrospective analysis

Abstract: Background: End-of-life (EOL) chemotherapy administration rates for solid tumours are 12-20% and are associated with a reduced quality of life, increased hospitalisation and incidence of death within an acute care facility. Aim:We sought to determine the rate of EOL chemotherapy in government and private hospitals and determine the impact on hospitalisations and location of death in lung and pancreatic cancer patients.Methods: Data were obtained from the Queensland Oncology Repository between 2005 and 2014. Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…There were no significant differences in end-of-life anticancer therapy use between the three stratification levels, contrasting reports of more intensive end-of-life treatment in university hospitals than in smaller hospitals. 8 , 23 Norway’s public health care system ensures cancer treatment according to national anticancer therapy guidelines with negligible patient cost and has few private for-profit clinics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no significant differences in end-of-life anticancer therapy use between the three stratification levels, contrasting reports of more intensive end-of-life treatment in university hospitals than in smaller hospitals. 8 , 23 Norway’s public health care system ensures cancer treatment according to national anticancer therapy guidelines with negligible patient cost and has few private for-profit clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-six started chemotherapy at a median of 36 (IQR 25-42) days and stopped at a median of 33 days (IQR 21-41) before death. Thirty patients started chemotherapy at a median of 18 days (IQR [12][13][14][15][16][17][18][19][20][21][22][23][24][25], with discontinuation at a median of 15 (IQR 10-21) days before death. Breakdown per group is reported in Table 2.…”
Section: Conventional Chemotherapy In the Last 3 Monthsmentioning
confidence: 99%
“…Despite evidence in multiple studies, 4 , 5 , 10 the number of patients near the end of life who receive chemotherapy has not decreased. It has been reported that >10% of patients with breast, 11 , 12 gastrointestinal, 8 , 13 and other 2 , 3 , 9 , 14 cancers receive palliative chemotherapy during the last four weeks of their lives. Several studies have identified younger age as a predictor for chemotherapy use during the last months of life.…”
Section: Discussionmentioning
confidence: 99%
“…According to Allen et al, 9–12% of lung and pancreatic cancer patients received EOL chemotherapy, with a higher prevalence in males with advanced metastatic cancer [ 47 ]. This was associated with higher rates of deaths within an acute care facility [ 47 ].…”
Section: Introductionmentioning
confidence: 99%